MERUBAH KONSEP DIRI NEGATIF REMAJA DENGAN BIBLIOTHERAPY - FADHILAH SYAFWAR (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
It is a fact that the symptom of misbehaviour among teenagers is not suddenly occurred. It could be caused by several factors such as lack of social supports from family as well as peer. One of other contributing factors is self-concept on negative aspects. Negative self-concept is potentially to be changed by using bibliotherapy. Bibliotherapy could scientifically be used as therapy to change self-concept from negative ones to the positive ones. The bibliotherapy might be implemented using individual, group, and classical approach. These approaches could be executed by counsellors to help teenagers have a positive self-concept. Kata kunci: merubah, konsep diri negatif, remaja, bibliotherapy